Penggunaan E-Modul Pembelajaran IPA Terhadap Hasil Belajar Siswa SMP - sri rezeki; Marjanah Marjanah; Dini Fitria (Universitas Nusantara PGRI Kediri, 2024)
This research aims to determine the effect of using E-Modules Science learning to improve student learning outcomes at SMPN 6 Langsa. This research uses quantitative research withthe True method Experimental design and pretest-posttestcontrol group design. Sample of this research are students of class VII-1 and VII-2 of SMPN 6 Langsa with a total of 54 students student. The research results show the average pretest scorefor the experimental class amounted to 43.29 (low) andthe control class amounted to 33.20 (very low) so The difference in the average pretest score between the two classesis 10.09. Whereas The average posttest score for the experimental class was85.25 (high) and the control score was 70.04 (medium) so the difference between the two classes is 15.21 with hypothesis test value tcount = 15.05 > ttable= 2.006. Thus you can it is concluded that Ha is accepted and Ho is rejected, meaning that there is an influence significant in the use of Science learning E-Modules to improve student learning outcomes at SMPN 6 Langsa